Congenital cystic adenomatoid malformation: a rare serial case report - Haryono, Dedy C.; Kartika, Muhammad; Hayuningrat, Prima K.; Ismail, Darmawan (International Surgery Journal, 2021)
Congenital cystic adenomatoid malformation (CCAM) is a rare congenital lung malformation which a part of the lung becomes polycystic. CCAM accounts for 25% of congenital lung malformations and 95% of lung lesions. Case 1 was a 5-month-old female infant who was diagnosed with pneumothorax, with multiple cysts in the right lung, using chest computed tomography (CT). Thoracotomy lung resection was performed. Case 2 was one-day-old newborn infant who had respiratory distress with Downe score 3. Multiple cystic lesions with septations in left lung was observed on chest CT. Lobectomy inferior lobes of left lung was performed. Both patients were diagnosed as CCAM type 1 pathologically. CCAM can be detected in the gestation by ultrasonography or after delivery through the appearance of respiratory distress signs.